Hydrogenation catalyst for producing hydrogen peroxide
By using an amorphous catalyst support containing palladium and other metals, the high cost of existing Pd catalysts has been solved, enabling efficient and low-cost preparation of hydrogen peroxide.
Patent Information
- Application Number
- CN202480043190.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-26
- Filing Date
- 2024-06-20
- Publication Date
- 2026-02-03
AI Technical Summary
Existing Pd-based catalysts for the AO process to produce hydrogen peroxide are costly, necessitating the development of a hydrogenation catalyst with the same or higher activity and selectivity to reduce production costs.
A catalyst containing palladium (Pd) and other metals, along with an amorphous catalyst support composed of aerogel-like silica and alumina, with alumina molecules incorporated into the silica structure, and catalyst powder particles with a particle size between 100 µm and 200 µm, is used for the hydrogenation of quinone.
It achieves catalytic activity similar to or higher than that of single-metal Pd catalysts, while reducing catalyst production costs and improving the economics of the AO process.
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to an anthraquinone process (AO) for the manufacture of hydrogen peroxide, wherein the hydrogenation step is carried out by means of a catalyst which comprises, in addition to palladium (Pd), at least one further metal and an amorphous catalyst carrier. BACKGROUND
[0002] Hydrogen peroxide is one of the most important inorganic chemicals produced worldwide. Its industrial applications include textiles, pulp and paper bleaching, manufacture of organic synthesis (propylene oxide), inorganic chemicals and detergents, environmental and other applications.
[0003] The synthesis of hydrogen peroxide is mainly achieved by using the Riedl-Pfleiderer process (originally disclosed in U.S. Pat. Nos. 2,158,525 and 2,215,883), also known as the anthraquinone loop process or AO (auto-oxidation) process.
[0004] This well-known loop process typically uses the auto-oxidation of at least one alkylanthrahydroquinone and / or at least one tetrahydroalkylanthrahydroquinone (most often 2-alkylanthrahydroquinone) to the corresponding alkylanthraquinone and / or tetrahydroalkylanthraquinone, which results in the production of hydrogen peroxide.
[0005] The first step of the AO process is the reduction of a selected quinone (alkylanthraquinone or tetrahydroalkylanthraquinone) to the corresponding hydroquinone (alkylanthrahydroquinone or tetrahydroalkylanthrahydroquinone) in an organic solvent (usually a mixture of solvents) using hydrogen gas from any source and a catalyst. The catalyst used in the reduction step of the AO process is usually a metal-based catalyst with sufficient activity and selectivity to reduce the selected quinone to the corresponding hydroquinone (e.g., 2-alkylanthraquinone to 2-alkyl-9,10-anthrahydroquinone). Many metal-based catalysts have been developed to increase the activity and / or selectivity of the catalyst. Nowadays, in the industry, Pd catalysts comprising a catalyst carrier are mainly used. These catalysts usually have high activity and selectivity to reduce the quinone to the corresponding hydroquinone. However, due to the use of Pd as the active metal component, the production cost of the single metal Pd-based catalyst and thus the AO process is high. Several efforts have been made to provide hydrogenation catalysts suitable for the AO process which show the same or even improved activity and / or selectivity as the single metal Pd catalysts but can be produced at low production cost. One approach is to replace Pd at least partially with a cheap metal.
[0006] However, by replacing Pd with another metal, there is a risk that the catalyst loses its high stable catalytic activity and selectivity. Therefore, there is a need to provide hydrogenation catalysts suitable for the AO process which have at least the same good catalytic properties as the single metal Pd catalysts but can be produced at lower cost. Summary of the Invention
[0007] This invention relates to an anthraquinone (AO) method for producing hydrogen peroxide, wherein the hydrogenation step is carried out using a catalyst in the form of catalyst powder particles having an average particle size between 100 µm and 200 µm, used in a slurry, and wherein the catalyst comprises
[0008] -Palladium (Pd)
[0009] - at least one other metal, and
[0010] - An amorphous catalyst support comprising silica and alumina (SiAlO) in an aerogel physical form. x ( ), in which aluminum oxide is incorporated into the silicon dioxide structure at the molecular level. Detailed Implementation
[0011] Before describing the method of the present invention in detail, it should be understood that the present invention is not limited to the specific method conditions described herein, as such conditions can of course vary.
[0012] It should also be understood that the terminology used herein is not intended to be limiting, as the scope of the invention will be limited only by the appended claims.
[0013] Unless the context clearly indicates otherwise, as used herein, the singular forms “a / an” and “the” include both the singular and plural indicators. For example, “a compound” means one or more compounds.
[0014] As used herein, the terms “containing / contains / contained of” are synonymous with “including / includes” or “comprising / comprises”, and are inclusive or open-ended, and do not exclude additional, unlisted members, elements, or method steps. It will be understood that the terms “containing / contains,” “comprising / comprises,” and “comprised of” as used herein include the term “consisting of / consists / consists of.”
[0015] Throughout this application, the term “about” is used to indicate a value that includes the standard deviation of the error of the apparatus or method used to determine that value.
[0016] As used in this article, the term "average" is exponential average, unless otherwise specified.
[0017] As used herein, the terms “% by weight,” “wt.-%,” “weight percentage,” or “percentage by weight” are used interchangeably. The same applies to the terms “% by volume,” “vol.-%,” “vol. percentage,” or “percentage by volume,” or “% by molar,” “mol-%,” “molar percentage,” or “percentage by molar.”
[0018] The numerical ranges listed by endpoints include all integers and (where appropriate) fractions contained within that range (e.g., 1 to 5, which may include 1, 2, 3, 4 when referring to, for example, the number of elements, and may also include 1.5, 2, 2.75, and 3.80 when referring to, for example, the measurement). Endpoint listings also include the endpoint values themselves (e.g., 1.0 to 5.0 includes both 1.0 and 5.0). Any numerical ranges listed herein are intended to include all subranges contained therein.
[0019] As used herein, the term "amorphous" refers to a solid in which long-range atomic order is absent, unlike a solid known as a crystalline solid. The "amorphous" or "crystalline" properties of the catalyst support (i.e., the catalyst support of this invention) can be shown by X-ray diffraction spectroscopy (XRD).
[0020] As used in this article, the term "aerogel" refers to a solid and rigid material consisting of a bonded, cross-linked macromolecular framework (network) (e.g., a SiO2 network, also known as silica gel) obtained from a corresponding monomer.
[0021] As used in this article, the term "anhydrous" means a substance that does not contain water. Therefore, aluminum gel, for example, is aqueous, not anhydrous. While it is true that anhydrous sources can be provided in solutions or suspensions, it is still classified as anhydrous nonetheless.
[0022] All references cited in this specification are hereby incorporated in their entirety. In particular, the teachings of all references specifically mentioned herein are incorporated by reference.
[0023] Unless otherwise defined, all terms used in disclosing this invention, including technical and scientific terms, have the meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Further guidance is provided, including definitions of terms, to better understand the teachings of this invention.
[0024] In the following paragraphs, various alternatives, embodiments, and variations of the invention are defined in more detail. Each so-called alternative and embodiment, when the range of values for the same parameter is separated, can be combined with any other alternative and embodiment, and this applies to each variation unless explicitly stated otherwise or clearly incompatible. In particular, any feature indicated as preferred or advantageous can be combined with one or more other features indicated as preferred or advantageous.
[0025] Furthermore, in one or more embodiments, the specific features, structures, or characteristics described herein may be combined in any suitable manner as will be apparent to those skilled in the art from this disclosure. Moreover, while some embodiments described herein include certain features (in addition to those included in other embodiments), combinations of features from different embodiments are intended to be within the scope of the invention and are derived from different embodiments as will be understood by those skilled in the art.
[0026] This invention relates to an anthraquinone (AO) method for producing hydrogen peroxide, wherein the hydrogenation step is carried out using a catalyst in the form of catalyst powder particles having an average particle size between 100 µm and 200 µm, used in a slurry, and wherein the catalyst comprises Pd, at least one other metal, and an amorphous catalyst support comprising silica and alumina (SiAlO) in an aerogel physical form. x Alumina is incorporated into the silicon dioxide structure at the molecular level.
[0027] In a preferred embodiment of the invention, the catalyst comprises Pd, at least one other metal, and an amorphous catalyst support, the amorphous catalyst support comprising silica and alumina (SiAlO) in an aerogel physical form. x Alumina is incorporated into the silicon dioxide structure at the molecular level.
[0028] The AO method for producing hydrogen peroxide, which has yielded particularly favorable results in the presence of the catalyst according to the invention, is specifically described in Ullmann's Encyclopaedia of Industrial Chemistry, 5th edition, 1989, Vol. A13, p. 443 and thereafter.
[0029] According to the present invention, the catalyst is used in the form of catalyst powder particles in a slurry to hydrogenate a selected quinone to hydrogenated quinone. The catalyst powder particles have an average particle size between 100 and 200 µm, determined by methods well known to those skilled in the art (e.g., by sieving or by laser particle size determination). Preferably, the catalyst powder particles have an average particle size between 110 and 190 µm, more preferably between 120 and 180 µm, and even more preferably between 130 and 170 µm.
[0030] The catalyst used in the AO method of the present invention contains at least one other metal in addition to Pd, preferably selected from the group consisting of Fe, Cu, Co, Ni, Sn, Ga, Zn, Au, Ag, Pt, Bi, and Ru, or combinations thereof. More preferably, the at least one other metal is Co, Ni, Au, Ru, or a mixture thereof.
[0031] Furthermore, preferably, the catalyst contains one, two, or up to five other types of metals as active components besides Pd, selected from the group defined above. In particular, it is preferred that the catalyst contains one, two, or three other types of metals besides Pd. More preferably, the catalyst is a bimetallic catalyst, i.e., the catalyst contains Pd and one other type of metal.
[0032] In the catalyst of the present invention, Pd and at least one other metal may be in elemental form or in the form of compounds (such as salts or oxides). The catalyst preferably comprises elemental Pd and at least one other metal.
[0033] The amount of Pd present in the catalyst is preferably 0.1 to 2.5 wt.-% based on the total amount of the catalyst. More preferably, this amount is 0.1 to 2.0, even more preferably 0.2 to 1.5 wt.-%, and most preferably 0.3 to 1.0 wt.-%.
[0034] The at least one other metal is used in the catalyst in an amount preferably from 0.01 wt.-% to 2.0 wt.-%, more preferably from 0.05 to 1.5 wt.-%, and even more preferably from 0.1 to 1.0 wt.-%.
[0035] The amount of metal present in the catalyst used in the AO method of the present invention can be determined by any method known in the art, for example by using inductively coupled plasma optical emission spectrometry (ICP-OES).
[0036] The catalyst used in the AO method of this invention is an amorphous supported catalyst. The catalyst support comprises silica and alumina (SiAlO) in an aerogel physical form. xIn this type of silica, alumina is incorporated at the molecular level into the silica structure; that is, silica forms a bonded, cross-linked macromolecular framework (network), also known as silica gel, where alumina is incorporated at the molecular level. Therefore, alumina exists not only on the outer surface of the silica gel (e.g., as a coating) but also within the silica gel. This structure can be determined using transmission electron microscopy (TEM) and / or scanning electron microscopy (SEM) combined with energy-dispersive X-ray spectroscopy (EDX). Due to this structure, the resulting catalyst support is homogeneous, unlike supports in which the first oxide has been deposited and / or precipitated on the second oxide.
[0037] Silica-based aerogels are typically characterized by mesoporous networks, where the size of the interconnecting pores typically ranges from 0.5 to 100 nm and the average diameter is between 5 and 40 nm. They typically exhibit a g / cm³ content of 0.03 to 0.8 g / cm³. 3 Low packing density within the range.
[0038] The amorphous catalyst support of the present invention can be produced by any method known in the art, but typically the following two methods are used.
[0039] One method is described, for example, in US 2012 / 01223138 A1. In this variant of the possible production method, silica is mixed with an anhydrous alumina source (e.g., sodium aluminate) at a pH level above 11 and a temperature of 30°C to 90°C to form a suspension. The suspension is then optionally washed with water, and the catalyst support is separated from the water, dried, and / or calcined. The catalyst support produced in this way contains anions, such as Cl-, in addition to SiO2 and alumina. - (CO3) 2- (SO4) 2- (NO3) - The amount of these anions does not exceed 10% by weight of the catalyst support. Preferably, the amount of these anions is typically between 0.05 and 8 wt.%, more preferably between 0.5 and 6 wt.%, and even more preferably between 1.0 and 3 wt.% based on the total weight of the support. The amount of anions present in the catalyst support can be measured by any method known in the art, such as that described, for example, in US2012 / 01223138 A1.
[0040] Another possible method for producing the catalyst support of the present invention is the sol-gel method, as described, for example, in the publication of CMR Almeida et al., Advances in Colloid and Interface Science 282 (2020), 102189, pp. 1-25. In this method, alumina and silica sols are prepared separately in the presence of a liquid (typically ethanol) and HCl and NH4OH as common acidic and basic catalysts. The two sols are then brought together in the presence of a suitable catalyst to obtain an alumina-silica gel. Subsequently, silylation and drying steps are performed to obtain the desired amorphous catalyst support comprising silica and alumina (SiAlO4) in an aerogel physical form. x ( ), in which aluminum oxide is incorporated into the silicon dioxide structure at the molecular level.
[0041] According to the present invention, the amorphous catalyst support according to the present invention preferably contains 1 to 50 wt.-%, more preferably 3 to 30 wt.-%, or even more preferably 5 to 10 wt.-%, based on the total weight of the amorphous catalyst support.
[0042] The catalyst support of the present invention preferably has a spherical shape.
[0043] Furthermore, the BET surface area of the amorphous catalyst support is preferably determined by porosity measurements between 1 and 1000 m². 2 Between / g, more preferably between 50 and 800 m 2 Between / g, or even more preferably between 100 and 700 m 2 Between / g.
[0044] To obtain the catalyst used in the AO method of the present invention, Pd and at least one other metal are deposited on an amorphous catalyst support as described above. This can be accomplished by any suitable method known in the art. Preferably, the metal is deposited on the catalyst support by precipitation and / or impregnation; more preferably, both at least one other metal and Pd are deposited under precipitation conditions.
[0045] The source of Pd can be a palladium salt selected from chlorides or acetates, preferably chlorides, and more preferably H2PdCl4.
[0046] At least other metal sources are usually salts selected from the following groups: acetates, bromides, chlorides, and nitrates.
[0047] The precipitation step is preferably carried out in an alkaline medium having a pH in the range of 7 to 12, more preferably 8 to 11. Therefore, the alkaline medium can be obtained by using, for example, sodium carbonate, potassium carbonate, sodium hydroxide, potassium hydroxide, or ammonium carbonate.
[0048] Furthermore, it is preferred that the precipitation is carried out at a temperature between 50°C and 80°C, more preferably between 55°C and 75°C, and even more preferably between 60°C and 70°C.
[0049] The deposition of Pd and at least one other metal on the catalyst support can be performed simultaneously or subsequently. According to the invention, preferably, in the first step, at least one other metal and subsequently Pd are deposited on the amorphous catalyst support.
[0050] In each case, after precipitation deposition and / or impregnation deposition, the catalyst is filtered out, preferably washed with demineralized water, optionally reduced to obtain the metal deposited in elemental form on the catalyst support, and dried.
[0051] The reduction step can be carried out by any method known in the art. Preferably, it is carried out by using a reducing agent selected from the group consisting of: molecular hydrogen, hydrazine, hydrates, hydrogen-containing gases, ascorbic acid, formic acid, and formaldehyde. The reduction is preferably carried out at a temperature between 20°C and 200°C, more preferably between 20°C and 100°C.
[0052] Typically, deposited metals can be located at different positions on an amorphous catalyst support. Metals can be concentrated in a thin layer near the outer surface of the support, which can be termed an "eggshell pattern" or "eggshell profile." Metals can be concentrated in a thin layer below the surface but not penetrating to the center of the support, which can be termed an "egg white pattern (profile)." Metals can be concentrated in a small area near the center of the support, which can be termed an "egg yolk pattern (profile)," and metals can be uniformly distributed throughout the support. According to the present invention, Pd and at least one other metal typically exhibit an eggshell profile as determined by STEM & SEM-EDX analysis.
[0053] Pd and at least one other metal are preferably located in particulate form on an amorphous catalyst support. These metal particles preferably have a size between 1 and 50 nm, more preferably between 3 and 45 nm, as determined by STEM & SEM-EDX analysis.
[0054] The catalysts of the present invention typically exhibit at least 100% activity relative to the activity of the same catalyst in which at least one other metal is replaced by Pd. Preferably, the catalysts show at least 110% or at least 120% relative activity, i.e., improved activity relative to the activity of the same catalyst in which at least one other metal is replaced by Pd. The activity of the catalyst can be determined by measuring the conversion rate from alkylanthraquinone to alkylanthrahydroquinone, as described, for example, in US 2012 / 0123138 A1.
[0055] Furthermore, since replacing Pd with at least one other metal can reduce the production cost of the catalyst, and thus reduce the production cost of the AO process, without losing high catalyst activity.
[0056] The invention will be further illustrated by the following examples. It should be understood that the following examples are for illustrative purposes only and are not intended to limit the invention thereto. Example
[0057] The SiAlO used in the examples and according to the teachings of the present invention x The catalyst support is produced by one of the methods described above.
[0058] Example 1 - Pd / Co / SiAlO x catalyst
[0059] The catalyst was prepared in two steps. First, 10 g of SiAlO xThe support was added to 30 ml of demineralized water and stirred at 250 rpm. 2 g of Na₂CO₃ was added and the reaction mixture was heated to 70°C. 5.25 ml of acidic CoCl₂·6H₂O solution (20 g Co / L) was added at a rate of 1 ml / min. The reaction mixture was stirred for 15 min. The mixture was then decanted and washed three times with 30 ml of demineralized water. 30 ml of demineralized water was added again, and the mixture was heated to 50°C at 250 rpm. 0.3 g of formic acid (100%) was added. The catalyst was then decanted again and washed three times with 30 ml of demineralized water. The catalyst was placed in an oven at 110°C to dry for 12 h. Next, the catalyst was added to 30 ml of demineralized water again, heated to 70°C, and stirred at 250 rpm. 5.25 ml of H₂PdCl₄ solution (20 g Pd / L) was added at a rate of 1.7 ml / min. The mixture was stirred for 15 min. The catalyst was then decanted and washed three times with 30 ml of demineralized water. Another 30 ml of demineralized water was added, and the mixture was heated to 50°C at 250 rpm. 0.3 g of formic acid (100%) was added. The catalyst was then decanted again and washed three times with 30 ml of demineralized water. The catalyst was then placed in an oven at 110°C to dry for 12 h.
[0060] Deposited on support SiAlO x The concentrations of the metals were determined by ICP-OES. The Pd concentration was 1 wt.% and the Co concentration was 0.35 wt.%.
[0061] The determined activity of the catalyst was 107% of the relative activity of the 1.0 wt.% Pd catalyst. STEM & SEM-EDX analysis revealed the eggshell-like structure of the two metals. The metal particles, Pd & Co, had sizes between 3 and 17 nm, and the catalyst powder particles had an average particle size of 120 µm as determined by laser particle size analysis.
[0062] Example 2 - Pd / Ni / SiAlO x catalyst
[0063] The catalyst was prepared in two steps. First, 10 g of SiAlO xThe support was added to 30 mL of demineralized water and stirred at 250 rpm. 2 g of Na₂CO₃ was added and the reaction mixture was heated to 70°C. 3.5 mL of acidic NiNO₃ solution (20 g Ni / L, NiNO₃ dissolved in dilute HCl) was added at a rate of 1 mL / min. The reaction mixture was stirred for 15 min. The mixture was then decanted and washed three times with 30 mL of demineralized water. Another 30 mL of demineralized water was added, and the mixture was heated to 50°C at 250 rpm. 0.3 g of formic acid (100%) was added. The catalyst was then decanted again and washed three times with 30 mL of demineralized water. The catalyst was placed in an oven at 110°C to dry for 12 h. Next, the catalyst was added to 30 mL of demineralized water again, heated to 70°C, and stirred at 250 rpm. 5.25 mL of H₂PdCl₄ solution (20 g Pd / L) was added at a rate of 1.7 mL / min. The mixture was stirred for 15 min. The catalyst was then decanted and washed three times with 30 ml of demineralized water. Another 30 ml of demineralized water was added, and the mixture was heated to 50°C at 250 rpm. 0.3 g of formic acid (100%) was added. The catalyst was then decanted again and washed three times with 30 ml of demineralized water. The catalyst was then placed in an oven at 110°C to dry for 12 h.
[0064] Deposited on support SiAlO x The concentrations of the metals were determined by ICP-OES. The Pd concentration was 1 wt.% and the Ni concentration was 0.10 wt.%.
[0065] The determined activity of the catalyst was 121% of the relative activity of the 1.0 wt.% Pd catalyst. STEM & SEM-EDX analysis revealed the eggshell profile of the two metals. The metal particles Pd & Co had sizes between 5 and 41 nm, and the catalyst powder particles had an average particle size of 120 µm as determined by laser particle size analysis.
[0066] Example 3 - Pd / Au / SiAlO x catalyst
[0067] The catalyst was prepared in two steps. First, 10 g of SiAlO xThe support was added to 30 ml of demineralized water and stirred at 250 rpm. 2 g of Na₂CO₃ was added and the reaction mixture was heated to 70°C. 1.05 ml of acidic AuCl₃ solution (20 g Au / L) was added at a rate of 1 ml / min. The reaction mixture was stirred for 15 min. The mixture was then decanted and washed three times with 30 ml of demineralized water. Another 30 ml of demineralized water was added, and the mixture was heated to 50°C at 250 rpm. 0.3 g of formic acid (100%) was added. The catalyst was then decanted again and washed three times with 30 ml of demineralized water. The catalyst was placed in an oven at 110°C to dry for 12 h. Next, the catalyst was added to 30 ml of demineralized water again, heated to 70°C, and stirred at 250 rpm. 63 ml of H₂PdCl₄ solution (20 g Pd / L) was added at a rate of 1.7 ml / min. The mixture was stirred for 15 min. The catalyst was then decanted and washed three times with 30 ml of demineralized water. Another 30 ml of demineralized water was added, and the mixture was heated to 50°C at 250 rpm. 0.3 g of formic acid (100%) was added. The catalyst was then decanted again and washed three times with 30 ml of demineralized water. The catalyst was then placed in an oven at 110°C to dry for 12 h.
[0068] Deposited on support SiAlO x The concentrations of the metals were determined by ICP-OES. The Pd concentration was 1.2 wt.% and the Au concentration was 0.068 wt.%.
[0069] The determined activity of the catalyst was 155% of the relative activity of the 1.4 wt.% Pd catalyst. STEM & SEM-EDX analysis revealed the eggshell profile of the two metals. The metal particles Pd & Co had sizes between 4 and 22 nm, and the catalyst powder particles had an average particle size of 120 µm as determined by laser particle size analysis.
[0070] Example 4 - Pd / Ru / SiAlO x catalyst
[0071] The catalyst was prepared in two steps. First, 10 g of SiAlO xThe support was added to 30 ml of demineralized water and stirred at 250 rpm. 2 g of Na₂CO₃ was added and the reaction mixture was heated to 70°C. 1.05 ml of acidic RuCl₃ solution (20 g Ru / L) was added at a rate of 1 ml / min. The reaction mixture was stirred for 15 min. The mixture was then decanted and washed three times with 30 ml of demineralized water. Another 30 ml of demineralized water was added, and the mixture was heated to 50°C at 250 rpm. 0.3 g of formic acid (100%) was added. The catalyst was then decanted again and washed three times with 30 ml of demineralized water. The catalyst was placed in an oven at 110°C to dry for 12 h. Next, the catalyst was added to 30 ml of demineralized water again, heated to 70°C, and stirred at 250 rpm. 5.25 ml of H₂PdCl₄ solution (20 g Pd / L) was added at a rate of 1.7 ml / min. The mixture was stirred for 15 min. The catalyst was then decanted and washed three times with 30 ml of demineralized water. Another 30 ml of demineralized water was added, and the mixture was heated to 50°C at 250 rpm. 0.3 g of formic acid (100%) was added. The catalyst was then decanted again and washed three times with 30 ml of demineralized water. The catalyst was then placed in an oven at 110°C to dry for 12 h.
[0072] Deposited on support SiAlO x The concentrations of the metals were determined by ICP-OES. The Pd concentration was 1 wt.% and the Ru concentration was 0.08 wt.%.
[0073] The determined activity of the catalyst was 130% of the relative activity of the 1.2 wt.% Pd catalyst. STEM & SEM-EDX analysis revealed the eggshell profile of the two metals. The metal particles Pd & Co had sizes between 5 and 41 nm, and the catalyst powder particles had an average particle size of 120 µm as determined by laser particle size analysis.
[0074] These examples demonstrate that the supported bimetallic catalysts of the present invention exhibit activity in the same range or even better than the corresponding monometallic Pd catalysts.
Claims
1. An anthraquinone (AO) method for producing hydrogen peroxide, wherein the hydrogenation step is carried out using a catalyst in the form of catalyst powder particles having an average particle size between 100 and 200 µm, used in a slurry, and wherein the catalyst comprises Pd, at least one other metal, and an amorphous catalyst support comprising silica and alumina (SiAlO) in an aerogel physical form. x The alumina is incorporated into the silicon dioxide structure at the molecular level.
2. The method according to claim 1, wherein, The at least one other metal is selected from the group consisting of: Fe, Cu, Co, Ni, Sn, Ga, Zn, Au, Ag, Pt, Bi, and Ru, or combinations thereof.
3. The method according to claim 1 or 2, wherein, The catalyst is a bimetallic catalyst.
4. The method according to any one of the preceding claims, wherein, The catalyst contains 0.1 to 2.5 wt.% of Pd.
5. The method according to any one of the preceding claims, wherein, The at least one other metal is present in an amount of 0.01 wt.-% to 2.0 wt.-% based on the total amount of the catalyst.
6. The method according to any one of the preceding claims, wherein, Alumina is present in the amorphous catalyst support in an amount of 1 to 50 wt.% based on the total weight of the amorphous catalyst support.
7. The method according to any one of the preceding claims, wherein, Pd and at least one other metal are located on the amorphous catalyst support in an eggshell pattern.
8. The method according to any one of the preceding claims, wherein, This amorphous catalyst support has properties between 1 and 1000 m 2 Surface area between / g.
9. The method according to any one of the preceding claims, wherein, The catalyst is produced by depositing Pd and at least one other metal on the amorphous catalyst support.
10. The method according to claim 9, wherein, In the first step, at least one other metal and subsequently Pd are deposited on the amorphous catalyst support.
Citation Information
Patent Citations
Catalyst support and process for the preparation thereof
US20120123138A1
Production of hydrogen peroxide
US2158525A
Production of hydrogen peroxide
US2215883A
